Health-Care Technology Transfer: Expert and Information Systems for Developing Countries - Kahen, G.; Sayers, B. McA. (Methods of Information in Medicine, 1997)
Computer-based technologies such as information systems and expert systems have an undoubted contribution to health-care development in developing countries. This paper addresses the appropriateness of these technologies for developing countries, the criteria to be used in selection of the technology to be transferred, and the need for a systematic approach to evaluation. A conceptual model for assessing transferability so as to achieve an effective transfer, has been introduced. This requires not only an attempt to amplify the role of information and expert systems in health-care improvement and for socio-economic development, but the analysis of prior experience in transferring these technologies to developing countries. Following this approach, and using operational research techniques such as the Analytic Hierarchy Process, a subjective assessment model has been described that can systematically guide decision-making about computer-based health-care technology to be transferred to developing countries.
Keywords: Information Technology; Medical Expert Systems; Technology Transfer; Developing Countries